Psalms in an age of distraction: experiencing the restorative power of biblical poetry - Jones, Ethan C. (Baker Academic, a division of Baker Publishing Group, 2024)
"In our current age of distraction, the Psalms, as a rich collection of poems, remain ready to train our ears, steady our hearts, and teach us to pray and to extend our imagination so that we might flourish"-- Provided by publisher